Homology and teleosemantics: The problem of the identity of the biological trait - Torres Meléndez, Julio (2021)
Teleosemantic is the theory that proposes an explanation of mental representation on the basis of the Darwinian theory of biological function. Although Darwin explains biological traits for both historical and adaptationist causes, Papineau and other proponents of teleosemantic rely only on the adaptationist dimension of the theory to account for the identity of the biological trait. This is shown in the teleosemantic response to the possibility that an exact duplicate of a human arose from non-evolutionary causes (the swampman). Clarifying the question about the homological nature of the trait identity is central to addressing the swampman argument. This argument has been renewed in the form of an empirical counterexample: the existence of functional tetrachromacy, a condition that would constitute a real case of mental representation that is not the result of a selection process. I will argue that teleosemantics can respond to the tetrachromacy challenge on the basis of a true evolutionary conception of biological trait identity.